2015
DOI: 10.1186/s12982-015-0036-5
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Brazilian municipalities to hantavirus infections based on multi-criteria decision analysis

Abstract: BackgroundHantavirus infection is an emerging zoonosis transmitted by wild rodents. In Brazil, high case-fatality rates among humans infected with hantavirus are of serious concern to public health authorities. Appropriate preventive measures partly depend on reliable knowledge about the geographical distribution of this disease.MethodsIncidence of hantavirus infections in Brazil (1993–2013) was analyzed. Epidemiological, socioeconomic, and demographic indicators were also used to classify cities’ vulnerabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 28 publications
1
18
1
10
Order By: Relevance
“…The increase of hantavirus incidence rate observed during 2010 in Barbados could be due to enhanced surveillance due to an ongoing dengue epidemic and thus greater awareness among physicians for persons presenting with dengue-like symptoms. The mean annual incidence rate observed in this study 33.03 cases per 100,000 person-years is higher than that reported from other countries including Brazil (1.0 cases/100,000 population), USA (0.009 cases/100,000 population), Chile (0.29 cases/100,000 population) even China (1.5 cases/100,000 population) (13,15,16). This may be due to a difference in the level of clinical suspicion, testing available and offered or the type of hantavirus infection, mild HFRS compared to HPS.…”
Section: Seasonalitycontrasting
confidence: 62%
See 1 more Smart Citation
“…The increase of hantavirus incidence rate observed during 2010 in Barbados could be due to enhanced surveillance due to an ongoing dengue epidemic and thus greater awareness among physicians for persons presenting with dengue-like symptoms. The mean annual incidence rate observed in this study 33.03 cases per 100,000 person-years is higher than that reported from other countries including Brazil (1.0 cases/100,000 population), USA (0.009 cases/100,000 population), Chile (0.29 cases/100,000 population) even China (1.5 cases/100,000 population) (13,15,16). This may be due to a difference in the level of clinical suspicion, testing available and offered or the type of hantavirus infection, mild HFRS compared to HPS.…”
Section: Seasonalitycontrasting
confidence: 62%
“…9). (13,14). The increase of hantavirus incidence rate observed during 2010 in Barbados could be due to enhanced surveillance due to an ongoing dengue epidemic and thus greater awareness among physicians for persons presenting with dengue-like symptoms.…”
Section: Seasonalitymentioning
confidence: 99%
“…HPS studies elsewhere have found that most individuals affected by HPS participate in agricultural or forestry activities [30; 40; 41; 42; 72]. This connection exists because HPS transmission requires contact between humans and aerosolized excreta of infected rodents, which is most likely in this demographic group.…”
Section: Discussionmentioning
confidence: 99%
“…The Human Development Index (HDI) is a summary measure of average achievement in key dimensions of human development and socioeconomic status of the populations, and includes elements of life expectancy, income (GDP/capita), and education. HDI is thus a measure of human development and poverty, and can be used as a proxy of the socio-economic factors (education, poverty and health) that influence HPS risk [42]. HDI data at the municipality level were extracted from IBGE (www.ibge.gov.br) website, with data available for 1991, 2000, and 2010.…”
Section: Methodsmentioning
confidence: 99%
“…Di Jepang, wabah penyakit Hanta terjadi tahun 1960an dan tahun 1985 tidak ada lagi laporan kasus Hanta pada manusia di Jepang, meskipun secara serologis, tikus R. norvegicus mengandung antibodi terhadap Hantavirus (Lokugamage et al 2004). Selain di Asia (Johansson et al 2010), virus ini juga ditemukan di beberapa negara di Eropa (Mailles et al 2005;Zeimes et al 2012), Rusia (Klempa et al 2008), Afrika (Klempa et al 2012;Sumibcay et al 2012) dan Amerika (Firth et al 2012;de Oliveira et al 2015).…”
Section: Situasi Infeksi Hantavirus DI Duniaunclassified